Effects of Culling on Planting Stock Production in Teak Nursery - Subramanian, K.; Gadbail, V. M.; Rambabu, N.; Jha, Mohan (Indian Forester, 1995)
This paper deals with the effect of culling on production on teak planting stock. Culling produces uniform and better quality seedlings.